Influence of magnetic in Be-stars disk formation due to rotation in line driven in stellar winds - Curé, Michel (2001)
Line driven wind theory has been improved including non-spherical expansion in order to study its influence upon disk formation in early-type stars. Assuming that magnetic field controls the flow geometry, the plasma must flow downstream through open magnetic field lines. It is found that in the polar direction rapid flow tube divergence almost does not modify the location of the critical (singular) point and the calculated terminal velocity is incremented about 400 km/sec. On the other band in the equatorial direction, for a fast rotation case, the location of the critical point is unchanged and the terminal velocity shows slightly variations of about 50 km/sec. This conclusion is the polar direction is contrary to previous results, where the finite disk correction has not been taken into account. These results suggest, that open magnetic field lines do not influence disk formation in Be-stars.